Post-inflammatory hyperpigmentation after carbon dioxide laser: review of prevention and risk factors - Bin Dakhil, Alhanouf; Shadid, Asem; Altalhab, Saad (Dermatology Reports, 2023)
The CO2 laser has been widely utilized in dermatology; its expanding clinical applications include the management of neoplastic lesions, benign growths, cosmetic conditions, and reactive disorders. The laser’s popularity is mainly due to the high precision and short recovery time this technology provides. However, postinflammatory hyperpigmentation (PIH) has been one of the challenging adverse effects of the CO2 laser. Therefore, several modalities have been studied for the prevention of PIH following CO2 laser treatment. This review aims to analyze the incidence of PIH after CO2 laser therapy, identify its risk factors, and assess the efficacy of the examined treatment modalities in preventing PIH. Pubmed and Embase databases were searched for this study, and relative clinical trials were included in the review. Descriptive findings – including age, gender, skin type, types of intervention, and incidence of PIH – were reported. When appropriate, the incidence of PIH was compared across each possible individual factor, such as skin type, gender, and type of intervention. A total of 211 articles were identified, and 14 relevant articles were included in this review. Seventy percent of the subjects were females (n=219), and 30% were males (n=94), with a mean age of 30 years (SD=7.8). The most common skin types were type IV (59%) followed by type III (25%). In total, eight studies investigated the prevention of PIH. The incidence of PIH after CO2 laser significantly varies between studies and differs based on the type of intervention. The studies indicate that the use of Clobetasol propionate 0.05% and fusidic acid cream appeared to effectively reduce PIH, recording an incidence rate of 39% and 53.3%, respectively. The Fitzpatrick-skinphenotype did not appear to influence the risk of PIH. There is a lack of high-powered clinical studies analyzing the incidence of PIH after CO2 laser treatment and the associated risk factors. PIH occurrence may be related to inflammation resulting from thermal damage by the CO2 laser. Consequently, the use of postoperative topical medications with anti-inflammatory properties might reduce its incidence. The use of ultra-potent topical corticosteroids and topical fusidic acid appeared to reduce PIH, possibly reducing postoperative inflammation effectively. Similarly, platelet-containing plasma may be beneficial in reducing CO2 side effects, including PIH. However, more studies are needed to further establish the influence of skin type on PIH and investigate modalities to reduce PIH occurrence after CO2 laser use.